Virtual programming environments and simulations in favor of active learning of programming - Czakóová, Krisztina (International Journal of Advanced Natural Sciences and Engineering Researches, 2023)
Microworlds are environments that allow the user to directly experience in a virtual simulation environment. It can also be understood as a carefully designed, constantly expanding software environment that focuses on learning certain concepts, phenomena or relationships within a clearly defined area. It is an environment where the students have a specific space for discovery and investigation, where to a certain extent they can define the goals and learning activities. Based on this concept, learning is supported, assisted and regulated, but not strictly directed or dictated in any way. One of the great advantages of microworlds (virtual program environments) is that they have a simple and low number of syntactic units. Microworlds are built on metaphors. They ensure the development of a colorful set of problems, which are directly related to the user's (student's) life experience. The instructions executed by an object in the given simulation environment are always visible. The order of execution allows students to understand thesemantics of the input control constructs. In this paper, we would like to present child-oriented programming languages (microworlds also known as mini languages), which can be powerful tools for introducing students to the world of programming languages, as well as providing a virtual space for the development of algorithmic thinking. It is advantageous if the program environment has a structured editor, which helps the student to eliminate syntactic errors. These program environments are classified and evaluated by taking these aspects into account and analyzing additional characteristic properties.